2010
DOI: 10.1038/ejhg.2010.63
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation profiling of human placentas reveals promoter hypomethylation of multiple genes in early-onset preeclampsia

Abstract: Preeclampsia and intrauterine growth restriction (IUGR) are two of the most common adverse pregnancy outcomes, but their underlying causes are mostly unknown. Although multiple studies have investigated gene expression changes in these disorders, few studies have examined epigenetic changes. Analysis of the DNA methylation pattern associated with such pregnancies provides an alternative approach to identifying cellular changes involved in these disorders. We analyzed methylation of 1505 CpG sites associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
154
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(170 citation statements)
references
References 45 publications
14
154
1
1
Order By: Relevance
“…Fetal DNA is hypomethylated, and because TLR9 senses hypomethylated DNA normally found in abundance in microbial DNA, we hypothesized that it might sense fetal DNA and provoke an inflammatory reaction possibly leading to PTB (21). In this study, we report that human fetal DNA can indeed activate TLR9 in vitro.…”
mentioning
confidence: 67%
“…Fetal DNA is hypomethylated, and because TLR9 senses hypomethylated DNA normally found in abundance in microbial DNA, we hypothesized that it might sense fetal DNA and provoke an inflammatory reaction possibly leading to PTB (21). In this study, we report that human fetal DNA can indeed activate TLR9 in vitro.…”
mentioning
confidence: 67%
“…29 The parent-of-origin imprinting of many genes in placenta is likely to play key roles in various aspects of placental function, including trophoblast cell proliferation, differentiation, angiogenesis and transportation of nutrients. [30][31][32] Deletion of H19 gene and the H19/Igf2-imprinting control region (also known as H19 DMD) leads to increased levels of Igf2 and fetal overgrowth as well as hyperplasia of all layers in the placenta. 33 It has long been suggested that the increase in placenta weight in these knockout mice results from the doubling of all Igf2 transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown previously that the methylation pattern of many genes differ between placentas from women with PE compared to controls. 36 In addition to ACOX2, we identified nine other genes whose transcription levels were correlated to both PE status and lipid levels ( Table 2). Even though these show lower statistical significance compared with ACOX2, we cannot exclude any of these genes from being as important in relation to developing both PE and CVD.…”
Section: Discussionmentioning
confidence: 99%